Chain modeling for the biogeochemical nexus of cadmium in soil–rice–human health system - Jintao Yang; Jinfeng Wang; Xiaoyong Liao; Huan Tao; You Li (Environment International, 2022)
This paper presents a novel chain model named soil–food–human (SFH) for clarifying the biogeochemical cascades among the triple challenges of cadmium contamination, food safety, and related public health effect. The model was developed based on the integration of spatial distribution pattern of soil environment and the biogeochemical process of cadmium in soil–rice–human health, and it was validated through a case study. In soil environment terms, SFH predicted the spatial distribution of soil properties with an average prediction accuracy of 82.28%. In food production terms, the SFH can identify the safe production zones for planting rice and unsafe area for adjusting cropping systems with a relative error of 39.41%. In food consumption terms, SFH mapped the high-resolution map of cadmium exposure dose, which gives a new solution to assess the food safety risks for self-sufficient populations. For the health effect of rice cadmium exposure, SFH simulated the spatiotemporal pattern of urinary cadmium based on toxicokinetic which revealed the health effect of rice cadmium exposure. The chain model provides a new insight in understanding the biogeochemical cascades between food production, food safety, and public health, making it possible to develop a comprehensive strategy to tackle cadmium pollution in soil–rice–human health system.